2016
DOI: 10.2217/pgs-2016-0077
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experiences with Pharmacogenetic Testing in a Primary Care Setting

Abstract: Aim:To investigate patient experiences with pharmacogenetic (PGx) testing. Methods: Patients were offered PGx testing through a study on pharmacist-assisted delivery of PGx testing and invited to complete pre-and post-testing surveys about their experience. Results: Of 63 patients tested, 17 completed the baseline survey (27%). Interest in testing was mostly impacted by desire to inform selection of best treatment (n = 13). Seven of 12 patients that completed the follow-up survey indicated that their provider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 32 publications
5
69
1
Order By: Relevance
“…Physicians completed surveys at two time points, and chart reviews were conducted at three time points. Findings from the patient perspective are reviewed in a separate manuscript [35]. The study was approved by the Duke University Health System's Institutional Review Board (Pro#00031122).…”
Section: Methodsmentioning
confidence: 99%
“…Physicians completed surveys at two time points, and chart reviews were conducted at three time points. Findings from the patient perspective are reviewed in a separate manuscript [35]. The study was approved by the Duke University Health System's Institutional Review Board (Pro#00031122).…”
Section: Methodsmentioning
confidence: 99%
“…Provider use and attitudes : Studies in which results were delivered to prescribers enabled an examination of how frequently they interfaced with the information and their attitudes about its value. Studies in which providers initiated SLCO1B1 testing generally reported low testing uptake . Studies delivering SLCO1B1 results to providers through the EHR without provider initiation have reported providers’ EHR transactional data.…”
Section: Resultsmentioning
confidence: 99%
“…Prescribing behavior and prescriptions : Most studies have reported or are actively collecting data on the impact of SLCO1B1 results on medication prescriptions, measured from either the EHR or the provider or patient report. Some studies of pharmacogenetic panel testing have reported only composite medication changes, whereas small pilot studies have reported specific cases where SLCO1B1 results guided therapy . Large studies with SLCO1B1 CDS alerts have reported counts of medication changes attributed to pharmacogenetic results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, pharmacists have the foundational education and training to interpret pharmacogenomic results given their expertise in pharmacokinetics, drug metabolism, and medication adverse effect profiles . Pharmacists may use pharmacogenomic results to tailor treatment plans for patients with depression to reduce the risk of adverse effects and increase drug tolerability, ultimately improving the patient experience …”
Section: Discussionmentioning
confidence: 99%